(untitled) (Hoboken, N.J., 2007)
This book aims to stimulate and promote the wide-ranging aspects of green chemistry and its major role in ensuring sustainable development.
Keywords: Environmental chemistry,Environmental management,Hóa học môi trường,Quản lý môi trường; Industrial applications,Ứng dụng Công nghiệp